2016
DOI: 10.1016/j.juro.2016.02.2969
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Radioligand Therapy with 177 Lu Labeled Prostate Specific Membrane Antigen Ligand for Imaging and Therapy in Patients with Metastatic Castration Resistant Prostate Cancer

Abstract: Radioligand therapy with (177)Lu-PSMA-I&T appears to be safe and active in heavily pretreated patients with metastatic castration resistant prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
131
1
12

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 174 publications
(149 citation statements)
references
References 21 publications
5
131
1
12
Order By: Relevance
“…In an initial study in mice, it has a highly efficient internalisation into prostate cancer cells with approximately 75% of the peptide bound to the cell internalised after 3 h of incubation 22. A similar small molecule PSMA peptide ending with a different chemical conjugation ( 177 Lu PSMA‐I&T) also appears effective as a therapeutic agent in a number of published studies 3, 2118, 23 …”
Section: Labelling Of Lu 177 With Psma Peptides: Different Available mentioning
confidence: 99%
“…In an initial study in mice, it has a highly efficient internalisation into prostate cancer cells with approximately 75% of the peptide bound to the cell internalised after 3 h of incubation 22. A similar small molecule PSMA peptide ending with a different chemical conjugation ( 177 Lu PSMA‐I&T) also appears effective as a therapeutic agent in a number of published studies 3, 2118, 23 …”
Section: Labelling Of Lu 177 With Psma Peptides: Different Available mentioning
confidence: 99%
“…PSMA ligand PET/CT has an evolving role in PSMA-targeting treatments (e.g., radioligand therapy), evaluating target expression and therefore potentially predicting response (62)(63)(64). A rare but potential limitation is absent or low PSMA expression (e.g., in visceral metastases) in advanced disease, which may be related to therapy-induced specific biologic subtypes (e.g., neuroendocrine differentiated PC) (65,66).…”
Section: Advanced Diseasementioning
confidence: 99%
“…A variety of PSMA ligands for radioligand therapy (RLT) have been developed in recent years (5). Several studies using 131 I-or 177 Lu-labeled PSMA ligands for RLT reported reductions in tumor volume and serum prostate-specific antigen (PSA) levels (3,(6)(7)(8)(9)(10). For the assessment of a new radiopharmaceutical, dosimetry is essential to aim for the optimal therapeutic response with limited side effects.…”
mentioning
confidence: 99%